Peningkatan Partisipasi Dan Hasil Belajar Matematika Melalui Strategi Pembelajaran Tutor Sebaya(PTK Bagi Siswa Kelas VIII A Semester Genap SMP Negeri 3 Gondangrejo Tahun 2013/2014) - Mulyoto, Danang Joko, Rita P. Khotimah, S.Si, M.Sc (2016)
Involve students learning less will result in students' understanding of the material that is less study results less than the maximum. This study aimed to describe the increase in participation and mathematics learning outcomes for students of classes VIII A of SMP Negeri 3 Gondangrejo with peer tutoring learning strategies in the learning of mathematics. This study includes classroom action research. The subjects in this study were teacher as implementers of action and VIII A grade students as recipients action. Data collection techniques observation, testing, field notes and documentation. Data were analyzed comparatively and interactive. The validity of the data by triangulation of sources and methods. The results of the study, the first increase in the participation of students, namely (a) motivation in doing the task of initial conditions 11,76%, cycle I 44,12%, and cycle II 61,76%, (b) provide opinions to solving the problem of the initial conditions 8,82 %, cycle I 35,29% , and cycle II 67,64%, and (c) provide feedback to the opinions of others on the initial conditions 8,82%, cycle I 38,23%, and cycle II 61,76%. It can be concluded that the application of peer tutoring learning strategies can increase participation and results of students' mathematics learning.